2004
DOI: 10.1007/s00467-003-1380-1
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic fibrosing dermopathy in pediatric patients

Abstract: Nephrogenic fibrosing dermopathy (NFD) is a rare and recently recognized sclerosing skin disorder of unknown etiology. Reported cases have occurred in patients with chronic renal failure, with or without renal replacement therapy. All previous cases have been reported in older adult patients. We describe two pediatric patients who recently developed this condition and review the existing literature for NFD. Our patients included an 8-year-old boy on peritoneal dialysis with no prior renal transplant and a 19-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…NFD and CUA thus may represent different parts of the same disease spectrum. Before the diagnosis of CUA, our group published the skin findings in this patient as a case of NFD in pediatrics (14). STS therapy was not administered in this patient until the diagnosis of CUA was established.…”
Section: Discussionmentioning
confidence: 99%
“…NFD and CUA thus may represent different parts of the same disease spectrum. Before the diagnosis of CUA, our group published the skin findings in this patient as a case of NFD in pediatrics (14). STS therapy was not administered in this patient until the diagnosis of CUA was established.…”
Section: Discussionmentioning
confidence: 99%
“…NSF has been reported in one 6-year-old patient and in older children after administration of the least stable linear agents to children with renal impairment (Dharnidharka et al 2007;Foss et al 2009;Jain et al 2004). Recent research on the prevalence of NSF in children identified 20 pediatric cases, 12 of which had documented gadolinium exposure (K. Darge, Personal communication).…”
Section: Gadolinium-based Contrast Mediamentioning
confidence: 93%
“…Proinflammatory processes, coagulation abnormalities, or recent vascular injuries are thought to promote the onset of NSF, whereas some patients suffered coincidentally from malignancy, metabolic acidosis, or hepatic disease (2). In detail, there is a number of case reports or small case series of patients with NSF who had an acute occlusion of their dialysis access (23,43), required creation of arteriovenous fistula (23,50,51), an angioplasty (50), suffered from deep venous thrombosis (7,44), pulmonary embolism (52), antiphospholipid antibody syndrome (7,27,45,53), protein C deficiency (54,55), renal vein thrombosis of the transplanted kidney (8), an atrial clot (56), peripheral vascular occlusion (43), transient ischemic attacks (43), multiple brain infarcts (43), an episode of atheroembolism (45), graft failure (42,47,48,52,(54)(55)(56), shock (8,50), multiple myeloma (44), lymphoproliferative disorder (48), brain tumor (23), infections (7,48,50), nonspecific inflammation (42), systemic lupus erythematodes (57), hepatic disease (23,45,53), or metabolic acidosis (13,50,54,55). Marckmann et al (25) found in a small case-control study that among CKD patients exposed to Gd-CA those who developed NSF had higher serum calcium and phosphate levels and received higher doses of erythropoietin than those who did not.…”
Section: Co-morbiditymentioning
confidence: 99%